ChemInform Abstract: Capture of in situ Generated Diazo Compounds or Copper Carbenoids by Triphenylphosphine: Selective Synthesis of trans‐Alkenes and Unsymmetric Azines via Reaction of Aldehydes with Ketone‐Derived N‐Tosylhydrazones. Issue 6 (11th February 2014) - Sha, Qiang; Ling, Yifei; Wang, Wenyong; Wei, Yunyang
Abstract The reaction of tosylhydrazones with aldehydes affords unsymmetrical azines (III) and (V).